2022
DOI: 10.1002/adom.202202208
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Assisted Synthesis of Large‐Size 2D Bismuth Telluride Flakes for Broadband Photodetection up to 2 µm

Abstract: remote sensing, military reconnaissance, and medical examination. [2] Recently, photo detectors based on 2D materials and their heterostructures have attracted more and more attention. Thanks to diverse electronic band structures, 2D materials can cover a wide spectral range from ultraviolet-visible-infrared (IR)-terahertz (TH) frequencies. [3] Typical 2D materials include graphene, black phosphorous (BP), and transition metal dichalcogenides (TMDCs). Unfortunately, graphene photodetectors are limited due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Bi 2 Te 3 has a layered structure with a rhombohedral system of D 3 d ( R 3 m ) space group, as depicted in Figure a. A single Bi 2 Te 3 layer consists of five alternating atoms in order of Te–Bi–Te–Bi–Te .…”
Section: Resultsmentioning
confidence: 99%
“…Bi 2 Te 3 has a layered structure with a rhombohedral system of D 3 d ( R 3 m ) space group, as depicted in Figure a. A single Bi 2 Te 3 layer consists of five alternating atoms in order of Te–Bi–Te–Bi–Te .…”
Section: Resultsmentioning
confidence: 99%
“…The device structure is shown in Figure 1a, which is a vertical heterojunction composed of multilayer Bi 2 Se 3 and BP. Bi 2 Se 3 flakes are synthesized by chemical vapor deposition 24 and transferred onto SiO 2 /Si substrate by polystyrene-assisted method 34 (details are found in Supporting Information Figure S2 and Section 4). Then, the mechanically exfoliated BP nanosheet is transferred to Bi 2 Se 3 via polydimethylsiloxane (PDMS) to form a p−n heterojunction (Figure S3 and Section 4).…”
Section: Resultsmentioning
confidence: 99%
“…This is because the carrier recombination in the device is mainly Shockley−Read−Hall (SRH) recombination in the junction region, 39 and the high-quality interface inhibits SRH recombination and promotes carrier transport. Next, we calculate the responsivity (R) and detectivity (D*) of the Bi 2 Se 3 /BP heterojunction photodetector according to the formulas R = I ph /(PS) and 34 where I ph represents photocurrent (I ph = I light − I dark ), P is the laser power density, S is the effective light sensitivity area of the device, and Δf and i n represent bandwidth and equivalent noise current, respectively. The noise power spectra of Bi 2 Se 3 /BP photodetector at 0 bias are shown in Figure S12, which is 2 orders of magnitude lower than the Bi 2 Se 3 photoconductive photodetector (Figure S1d).…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen's dual role in acting as an etching agent and inhibiting MoO 3 precursor source poisoning has been systematically verified, underscoring its paramount significance in the growth process. It is reported that Bi 2 Te 3 thin films with controllable thickness (one to several layers) were successfully synthesized by H 2 -assisted CVD [95]. The growth rate of H 2 is as high as 48 μm min −1 , which is 10 times faster than that of conventional methods, because it has strong reducibility and substrate passivation.…”
Section: Vapor-assisted Growthmentioning
confidence: 99%